Enzyme-Activatable Fluorogenic Probes: Design Strategies, Biomedical Applications, and Future Perspectives - Yufan Fan; LeLe Liu; Hairong Zeng; Zeyu Wang; Xiaojun Peng; Zhuang Hu; Tony D. James; Guangbo Ge (Journal of the American Chemical Society, 2026)
Abstract Enzymes are pivotal regulators of cellular metabolism and organismal homeostasis, and their dysregulation is often associated with the onset and progression of disease. Therefore, accurate monitoring of the real activities of target enzymes is essential for deciphering biological mechanisms and gaining pathological insight. Through decades of iterative refinement, a diverse repertoire of enzyme-activatable fluorogenic probes (EAFPs) have been developed, enabling the capture of aberrant enzyme dynamics with high spatiotemporal resolution and multifunctional biosensing capabilities. In this context, we highlight the current state-of-the-art EAFPs, spanning fundamental design principles to proof-of-concept applications. First, the molecular engineering, sensing mechanisms, and design strategies of EAFPs are introduced. Next, a wide range of cutting-edge probes for imaging and sensing target enzyme(s) are presented, with emphasis on structural features, recognition mechanisms, and biomedical applications. Representative examples in biomarker imaging, disease diagnosis, drug screening, and therapeutic testing are highlighted to illustrate both the design principles and practical utility. Finally, the existing challenges and future trajectories for EAFPs in specific application scenarios are discussed. The insights presented here will inspire and accelerate the development of high-performance multifunctional EAFPs for both fundamental and translational research.